INVESTIGATING THE APPLICATION OF TRANSLATION TECHNIQUES BY STUDENTS IN TRANSLATING BY LAWS - Jefriadi; Havid Ardi (University of Kuningan, 2025)
The translation of legal documents, particularly bylaws, is fraught with empirical and theoretical challenges due to the precision required to uphold the original text's legal intent, authority, and clarity. Legal translation is not merely a linguistic exercise; it involves deep comprehension of both the source and target legal systems. the process of translating bylaws is often complicated by the necessity of maintaining a formal tone while ensuring that the legal meaning is preserved. The study utilized qualitative descriptive methods and the purposive sampling technique was employed to select participants based on specific criteria. The translation techniques in translating bylaws, conducted by sixth semester English Education students at Universitas Negeri Padang in 2024, there were 10 translation techniques used by translators and total of translation techniques used were 1364 times. From the 9 translation techniques, each one is ranked from the most frequently used to the least used: Established equivalent 743 times (54,5%), Literal Translation 185 times (15,6%), Calque 166 times (12,17%), Amplification with 92 times (6,74%), Transposition 89 times (6,52%), Borrowing 41 times (3,01%), Reduction 24 times (1,76%), Particularization 23 times (1,69%) and Variation with 1 time (0,07%). The percentage is a calculation of the total translation techniques used.